A survey of executive compensation contracts in China's listed companies - Yubo Li; Fang Lou; Jiwei Wang; Hongqi Yuan (China Journal of Accounting Research, 2013)
We analyze 228 executive compensation contracts voluntarily disclosed by Chinese listed firms and find that central-government-controlled companies disclose more information in executive compensation contracts than local-government-controlled and non-government-controlled companies. Cash-based payments are the main form of executive compensation, whereas equity-based payments are seldom used by Chinese listed companies. On average, there are no significant differences in the value of basic salaries and performance-based compensation in executive compensation contracts. But, compared with their counterparts in non-government-controlled companies, executives in government-controlled companies are given more incentive compensation. Accounting earnings are typically used in executive compensation contracts, with few firms using stock returns to evaluate their executives. However, the use of non-financial measures has increased significantly since 2007.
Keywords: 650; Executive compensation; Voluntary disclosure; Incentives; Performance measures